Konsep Amwal dalam Al-Qur'an dan Hadits - Surono, Yudi; Gunawan, Aan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The concept of amwal in the Qur'an and Hadith is an important topic in Islamic economic studies, which is related to the understanding of wealth, ownership, and management. Amwal, which means "property" or "wealth", is regulated in Islamic holy texts as a tool to achieve worldly and afterlife welfare, with an emphasis on justice, equitable distribution, and social responsibility. In the Qur'an, amwal is considered a trust from Allah that must be used wisely and not misused for purposes that are detrimental to oneself or society (QS. At-Tawbah: 34, Al-Baqarah: 261). The Hadith of the Prophet Muhammad SAW emphasizes the importance of using wealth for good, including giving alms, helping those in need, and maintaining a balance between personal needs and social obligations. This article aims to analyze the understanding and application of the concept of amwal in the Qur'an and Hadith, and how these principles can be applied in modern life to create a just and blessed economic system, in accordance with Islamic teachings.